Perceived Role of Social Media in the Vocabulary Development of University Students - Domingo, Dr. Mee Jay A.; Aguillon, Harvey John Tolentino (Allure Journal, 2021)
In the academe, stakeholders are starting to acknowledge the impact of social media in the teaching and learning process. Aware of this, the researchers conducted this study to determine the role of social media in the language learning experiences of students. Specifically, it identified the social media profile of the students and the platformsâ€™ perceived use and advantages to vocabulary development. In realizing its objectives, the study employed a descriptive research design that involved 83 university students from a state university in the Philippines. Respondents answered an online survey questionnaire, which was tried out first to potential respondents before its actual use. The researchers used descriptive statistics to make sense of the data gathered. Results show that the students have high social media engagement as manifested by the number of social media accounts that they created for themselves (the majority have two or more accounts) and the number of hours that they spend a day online (majority are online for at least three hours a day). All the respondents use Facebook.com, making it the most commonly used social media platform among them. In addition, the study found that students perceive social media as contributory and effective applications for the enhancement of language and vocabulary skills due to the mediaâ€™s accessibility, universality, ease of use, multimodality, general appeal, and its role in lowering communication anxieties. With these findings, educators are encouraged to explore the possibility of using social media platforms, preferably Facebook, as instructional media, specifically for the teaching of vocabulary.Â